Impacts of Artisanal Gold and Diamond Mining on Livelihoods and the Environment in the Sangha Tri-National Park (TNS) Landscape - Schure, J.; Ingram, V.J. (Center for International Forestry Research, 2009)
Gold and diamond mining constitute more than half of all mineral exploitation worldwide and an estimated 6 to 9 million artisanal miners are active in the gold and diamond sector. Africa hosts a third of the world’s natural mineral wealth, among which 65 percent of global diamond deposits. While mineral exploitation contributes to the livelihoods of many, it also generally leaves a negative impact on the environment, which may ultimately be detrimental to livelihoods. The consequences of mining for both the environment and livelihoods are of particular concern in important landscapes, such as the Sangha Tri-National Park (TNS) covering Cameroon, the Central African Republic and the Republic of Congo. This brief offers recommendations based upon an extensive study on the impact of artisanal gold and diamond mining in the Sangha Tri-National Park (TNS), which is a joint initiative of the Centre for International Forestry Research (CIFOR) and the International Union for Conservation of Nature, Central and West African Office (IUCN-PACO).